RESPON PERTUMBUHAN DAN PRODUKSI BEBERAPA KULTIVAR KENTANG HITAM (COLEUS TUBEROSUM) TERHADAP PEMUPUKAN NPK - Anisa Yosa Puri EP, Yudi Rinanto (BIOEDUKASI, 2013)
Black potatoes (Coleus tuberosus Benth.) is a crop that has a high carbohydrate content and resistance to pests and diseases better than other types of potatoes grown in the highlands. Productivity some of black potato?s cultivars grown by farmers varies between regions. The research was conducted to study the growth response and production of three cultivars derived from Blora, Sragen and Purwokerto on four levels of NPK fertilization there are without fertilizer, 3, 6 and 9 grams for each plant, respectively. Black potatoes were planted in polybags using bulbs that had germinated during one week.The results showed a dose fertilization and its interaction with the type of black potatoes kutivar not significantly affect observations on plant height, number of leaves, fresh weight of plant, dry weight of plant and tuber weight, but among cultivars showed differences in growth. The difference in growth between cultivars is not caused by fertilization treatment but causes by genetic differences. Cultivars derived from Sragen showes growth and tuber production better than the other cultivars.Keywords : Coleus tuberosum, black potato, resistance, fertilizer